Leadership styles of nursing professionals in preventive promotional areas of health facilities - Zambrano Castro, Hernán Luis (2025)
Objective. Determine the leadership style most developed by the nursing professionals in the promotional preventive areas of the Huánuco health network establishments. Methods. It was a descriptive, observational, prospective, cross-sectional study with 56 nursing professionals who work in the promotional preventive areas of the Huánuco health network establishments in 2016. The instruments used were the questionnaire on the general characteristics of the nursing professionals under study and the adapted short 5X form multifactorial leadership questionnaire. Results. The results were analyzed using the Chi Square test. Obtaining that 48,2 % of nursing professionals developed transformational leadership, on the other the transformational  leadership styles (p <0.041) which means that they were related to the development of some type of leadership, while transactional leadership (p <0,212) and corrective / avoidant leadership (p <0,813) are not related. Conclusion. The leadership style most developed by the nursing professionals in the promotional preventive areas of the Huánuco health network establishments was Transformational leadership